2007
DOI: 10.1111/j.1467-7652.2007.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically stable expression of functional miraculin, a new type of alternative sweetener, in transgenic tomato plants

Abstract: SummaryMiraculin is a taste-modifying protein isolated from the red berries of Richadella dulcifica , a shrub native to West Africa. Miraculin by itself is not sweet, but it is able to turn a sour taste into a sweet taste. This unique property has led to increasing interest in this protein. In this article, we report the high-yield production of miraculin in transgenic tomato plants. High and genetically stable expression of miraculin was confirmed by Western blot analysis and enzyme-linked immunosorbent assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
104
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 39 publications
2
104
0
3
Order By: Relevance
“…The transgenic tomato line 56B was produced in our previous work (Sun et al 2007). In brief miraculin encoding 660-bp DNA fragment was inserted into the XbaI/SacI sites of the plant transformation vectors pBI121 (Sun et al 2006).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The transgenic tomato line 56B was produced in our previous work (Sun et al 2007). In brief miraculin encoding 660-bp DNA fragment was inserted into the XbaI/SacI sites of the plant transformation vectors pBI121 (Sun et al 2006).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Therefore, we decided to produce recombinant miraculin in transgenic tomatoes. We developed transgenic tomato plants that accumulate significant levels of miraculin protein (Sun et al 2007), and the protein produced had almost same level of tastemodifying activity as native miraculin from miracle fruits. Furthermore, we characterized the miraculin accumulation pattern in the transgenic tomato fruits in detail and found that miraculin accumulation was highest in the exocarp (Kim et al 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…when these modified genes are expressed in them (Mandaokar et al, 2000). Tomato is an excellent plant for stably expressing transgenes, indicating a good target for genetic engineering (Kobayashi et al, 2003;Omura et al, 2007;Sun et al, 2007). These characteristics make it an attractive research target for practical application in food and agricultural industries.…”
Section: Insect Bioassaymentioning
confidence: 99%